Book exposition in Pranciškus Smuglevičius Hall of the Vilnius University Library: history, present, perspectives - Krakytė, Asta (Knygotyra, 2003)
Manuscripts and printed documents that have survived in the Vilnius University Library allow relating the origin of the Pranciškus Smuglevičius Hall exhibition to social-political changes in Lithuania of XIX c. After the 1830–1831 uprising the Vilnius University was closed by the Tsarist Russian government and in 1851 by joint efforts of count Eustachijus Tiškevičius and other enlightened Lithuanian enthusiasts a Museum of Antiquities of the Vilnius Provisional Archaeological Commission was established in 1855 in the premises of the former Vilnius University which displayed an outstanding collection of artistic works, minerals, archeology, numismatics, etc. After the 1863 uprising the Museum was closed and by a special commission headed by Ivan Kornilov was reorganized into the Vilnius Public Library officially opened on 5 June (24th of May in the old style) 1867. It is difficult to assert whether the exhibition in the former University Aula (newly decorated by Vasilij Griaznov) was prepared namely for the opening celebration, however Vilnius Public Library Guides which were published later (1879, 1904), Library Reports (1902–1910, 1914) and entries in the Visitors Book (first ones dated from 1858) witness that before the World War I there was a numerous (438 items) permanent exposition of manuscripts and books, compiled from old holdings of the Vilnius University Library, Central State Archives and newly acquired collections. As at that time Lithuania was only a province of the Russian Empire this exhibition as well as the activities of the Library strived not only for educational but also for propaganda goals, therefore it was only natural that the selection of exhibits have been tendentious enough although a significant part represented Lithuanian as well as European history of culture and book: XIII–XIV c. parchments, incunabula, XVI–XVII c. atlases, antique authors, humanistic works, privileges and decrees of Sigismundus I, Sigismundus II, Sigismundus III, writings of Nicolaus Christophorus Radivilus, Casimirus Leo Sapieha and other Lithuanian noblemen, publications of Franciscus Skorina, Mamonich Printers, the Statute of Lithuania, the Brest Bible, treatises by Petrus Skarga, Marcin Smiglecki etc. Upon the start of the World War I the work of the Library was interrupted, many valuable exhibits of the Museum, manuscripts and publications were plundered, part of the collections was taken to Russian libraries. There is scanty information about the fate of the P. Smuglevičius Hall exposition, yet we may surmise that it couldn’t escape war disasters. After the War and a turbulent period of 1918–1919 the Library renewed its activities as a sub-unit of the Polish Stephan Batory University. There is not much archival material from this period as well, however the publications of that time indicate that there was a public reading room in P. Smuglevičius Hall (in 1929 restored by a Polish painter Jerzy Hopen) and unceasing entries in the Visitors Book, information about ongoing seminars of librarians lead to supposition that the exposition has been re-established, and consistently continued up to the beginning of the World War II. In 1940–1945 the Library again experienced the stage of havoc and losses yet the staff managed to hide some of the collections and safeguard them from plunder and destruction. After the War due to changes of political situation the revival of the Vilnius University Library has been rather slow. There was shortage not only of experience, qualification but of funds and manpower as well. Notwithstanding this during first postwar years alongside cleaning of premises, recreation of collections, reader services the staff of the Library started to renew the P. Smuglevičius Hall exposition. By joint efforts of Prof. Levas Vladimirovas, Albina Jonaitienė, Janina Gutauskienė and other librarians of the Manuscript and Rare Book Department, the exhibition which represented not only the reality of the Soviet period, but the history of the Vilnius University, Lithuanian culture and book history as well, has been successfully recreated and with insignificant structural and thematic changes has been displayed in P. Smuglevičius Hall up to 1990. The extant records (1984–1986) of Nojus Feigelmanas, the former head of the Rare Book Department, allows to suppose that there was a scheme to establish a Book Museum on the basis of this long-lasting exposition of the Vilnius University Library. Regrettably this project has not been materialized and from 1991 up to the present the P. Smuglevičius Hall exhibition has stayed as a minor variant (about 30 items) of continual book exposition with a supplementary permanently changed thematic exposition of old publications, well attended by excursions and guests of the Vilnius University.